CHANGE MANAGEMENT AND EMPLOYEE PERFORMANCE OF HEALTH WORKERS IN RIVERS STATE - Isokariari, Orusoso Waite Lawson (American Journals, 2023)
Employee performance and adapting to change was the topic examined. Participants in this study are employed by one of the 346 primary healthcare (PHC) centres found in one of the 23 study LGAs. From the 23 LGAs in the state, 12 were chosen at random using multi-stage sampling; three from each senatorial district. Then, in each of the 12 LGAs, four Primary Health Facilities were chosen at random. Then, from among the chosen PHCs, health workers from various cadres were randomly selected using stratified selection. From each of the forty-eight (48) institutions, a random sample of 96 Community Health Extension Workers (CHEWs), 96 Community Health Officers (CHOs), 96 Nurses/Midwives, and 48 Doctors were taken. A total of 336 people were randomly selected for this analysis. This research was carried out using a descriptive cross-sectional methodology. In order to accomplish the goals of the study, five hypotheses were proposed and tested at the 0.05 level of confidence. Descriptive statistics (mean) were employed to examine the data, while the Spearman Rank Correlation Coefficient was used to evaluate the hypotheses. Health workers in Rivers State were found to benefit substantially from change management strategies like change communication and stakeholder engagement. Effective change communication techniques should be prioritised by the Health Care Management Board in order to foster a good and supportive work environment in which people may thrive despite change.
Keywords: Change Management, Employee Performance, Change Communication, Stakeholder Management, Work Quality, Employee Productivity